The relations between rectal shunt index and portal hypertension complications - T. SARIÇAM; E. VARDARELİ and H. YAVUZ and E. TOK and Y. KİŞİOĞLU and A. HARMANCI and E. ERENOĞLU (Turkish Journal of Gastroenterology, 2020)
-